25.0k views
0 votes
How to turn this equation:
y= -1.02(x-3)^2+9.25
into factored form

1 Answer

5 votes

Answer:


y=(102x-306-5√(3774))(102x-306+5√(3774))

Explanation:

You first equate it to zero to get:


-1.02(x-3)^2+9.25=0

Then solve using square root method


-1.02(x-3)^2=-9.25


(x-3)^2=(-9.25)/(-1.02)


(x-3)^2=(925)/(102)


x=3\pm\sqrt{(925)/(102)}

Or


x=3\pm{(5√(3774))/(102)}


x={(306\pm5√(3774))/(102)}

Now work it backwards


102x-(306\pm5√(3774))=0


(102x-306-5√(3774))(102x-306+5√(3774))=0

Hence the factored form is:


y=(102x-306-5√(3774))(102x-306+5√(3774))

User Brianhevans
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.